Challenges in Using Automated Decision-Making in Public Administration in Indonesia - Puspitasari, Kusuma Dewi; Wiryantiningsih, Endang (KnE Social Sciences, 2022)
President Jokowi’s program to downsize Echelons III and IV aimed to reduce the range of decision-making in the Government. Jokowi also hopes to use artificial intelligence (AI) systems to support and accelerate the state civil apparatus in carrying out their administrative duties, especially decision-making. AI can be used for speedy decisionmaking in the form of automated or algorithmically driven decision-making. However, Law number 30 of 2014 concerning Government administration only accommodates Government agencies and officials in making decisions or actions. Moreover, decisionmaking in public administration should comply with the general principles of good governance, be free from conflicts of interest, and is subject to administrative effort. This paper examined the challenges in automated decision-making in public administration. A normative judicial approach was used. The results showed that AI, especially algorithmically driven decision-making, should be designed to make fair, transparent, and reasonable decisions. The Government should also implement AI in ways that comply with good administration standards. AI application in public administration will require a fundamental change in the Government administration law. Therefore, it is necessary to amend Law number 30 of 2014 to grant limited authority around decisions or actions to be performed by AI. Keywords: artificial intelligence, automated decision-making, public administration, government administration law